Representações de professores sobre materiais didáticos impressos: EaD na Educação Especial - Bagetti, Aline (2007)
We looking for, in the decades of 60 and 70, time where it had an intense use of the educational resource didactic material, support know what the didactic material production bring us in Distance Education today. We lived in a military dictatorship that, consequently, reached the school, the professor s formation and the production of standardized and controlled book-texts for the perspective of the national security, introduced by North-American postwar politics, adjusted, in Brazil with the military government. Pedagogical practices emphasized, then, theories as the programmed instruction and the auto-instruction, which functioned as way of operationalization of the individuals behavior control. In this research, we judged relevant to search two types of printed didactic materials. The ones of the first type consist of materials produced in the seventies, produced by Minerva project destined for Supplementary Education. The same ones were sent to the students by correspondence and emphasized behavior theories, as the instructions previously cited. In this material, the activities planned to after class were directed and guided by professors. The ones of the second type are printed didactic materials, destined to Higher Education, produced by professors from Distance Graduation course in Special Education at UFSM, also sent to the students by correspondence. These also present instructional nature and activities guided by professor. In this way, some modifications happen in the current materials due to use of the computer and the Internet which become possible the materials improvement for the new times. It can be said that they are cybernetic materials. Thus, it became viable to problematize representations of the professors from Distance Graduation course in Special Education at UFSM, on EaD in the context of production of didactic materials this research entailed the research line: Formation, know and professional Development. We submit this research from the concepts of the Social Representations theory and we did half-structures interviews with the professors who had produced the printed didactic materials because this theory guides for the approach of the reality aspects that the professors' speeches allow to identify through the interviews. Starting from the research about representations, we establish categories of analysis that came out with the speeches, as team work, the specialists intervention, the improvement of the utilized technologies which allow an intense control on the pedagogical practices of the professors and on the students education. As a result, it can be noticed that the learning process in Distance Education is more controlled due to the use of a didactic material and communicational pedagogic strategies, typical of the control societies in the Deleuze s conception.